On the issue of creating an algorithm for assessing safety culture in modern healthcare institutions - Yavorovsky , O.P.; Serheta, I.V.; Brukhno , R.P.; Skaletskyi , Yu.M.; Chopchyk , V.D.; Varyvonchyk , D.V.; Zenkina, V.I. (Medicni Perspektivi, 2024)
Healthcare institutions with a high culture of patient safety are characterized by the appropriate level of mutual trust of employees, a general understanding of the importance of patient safety issues, the presence of an effective system of preventive measures to ensure the safety of both medical personnel and the patient, which has been implemented. Moreover, maintaining a high safety culture requires an understanding of certain norms of behavior and attitude towards the patient from the stand point of ensuring his maximum safety, which contributes to compliance with treatment standards and the development of safe behavior. The aim of the study was to create and scientifically substantiate an algorithm for analytical assessment of the level of safety culture in modern healthcare institutions. The research was conducted on the basis of the Dental Medical Center of Bogomolets National Medical University. Hygienic and medical-sociological methods and methods of expert assessment and statistical analysis were used in the work. Expert assessment maps of the leading components of safety culture served as the material of the conducted research. The organizational and target structure of the scientific work provided for the determination of the structural features of the leading components of safety culture and the development of a scoring scale for their assessment, the implementation of an expert evaluation of the specified components and the establishment of the degree of consistency of the opinions of experts, the calculation of the weighting coefficients of the influence of various components on the formation of a certain level of safety culture and the justification of objective statistical approaches to assessing the level of safety culture. In the course of the conducted research, a high degree of consistency of experts’opinions was revealed and the values of weighting coefficient swere calculated, which made it possible to develop generalized formulas for determining the values of indicators of the level of safety culture provision in modern healthcare institutions from the standpoint of assessing the degree of influence on the level of safety culture of the leading characteristics of dangerous actions of a person (doctor, specialist, etc.) (Component No. 1), identifying the degree of influence on the level of safety culture of both strengths and weaknesses in creating a safe medical environment (Component No. 2) and establishing the degree of influence on the level of safety culture of dangerous production factors inherent for medical environment (Component No. 3). It is substantiated that the process of creating an algorithm for analytical assessment of the level of safety culture in modern healthcare institutions should involve the implementation of the following stages: establishing the degree of expression of the leading indicators that are components of each of its main components, using special scales (1ststage), determining the values indicators of ensuring the level of patient safety culture for each of the components using the appropriate generalized formulas (2ndstage), evaluation and meaningful interpretation of the values of indicators of the level of safety culture based on quantitative criteria (3rdstage), determination of collective, group or personalized, according to the content, strategies application of preventive measures aimed at increasing the level of safety culture in each specific case (4thstage).